Design and Synthesis of Hepatitis B Virus (HBV) Capsid Assembly Modulators and Evaluation of Their Activity in Mammalian Cell Model - Karina Spunde; Brigita Vigante; Unda Nelda Dubova; Anda Sipola; Irena Timofejeva; Anna Zajakina; Juris Jansons; Aiva Plotniece; Karlis Pajuste; Arkadij Sobolev; Ruslan Muhamadejev; Kristaps Jaudzems; et al. (MDPI AG, 2022)
Capsid assembly modulators (CAMs) have emerged as a promising class of antiviral agents. We studied the effects of twenty-one newly designed and synthesized CAMs including heteroaryldihydropyrimidine compounds (HAPs), their analogs and standard compounds on hepatitis B virus (HBV) capsid assembly. Cytoplasmic expression of the HBV core (HBc) gene driven by the exogenously delivered recombinant alphavirus RNA replicon was used for high level production of the full-length HBc protein in mammalian cells. HBV capsid assembly was assessed by native agarose gel immunoblot analysis, electron microscopy and inhibition of virion secretion in HepG2.2.15 HBV producing cell line. Induced fit docking simulation was applied for modelling the structural relationships of the synthesized compounds and HBc. The most efficient were the HAP class compounds-dihydropyrimidine 5-carboxylic acid n-alkoxyalkyl esters, which induced the formation of incorrectly assembled capsid products and their accumulation within the cells. HBc product accumulation in the cells was not detected with the reference HAP compound Bay 41-4109, suggesting different modes of action. A significant antiviral effect and substantially reduced toxicity were revealed for two of the synthesized compounds. Two new HAP compounds revealed a significant antiviral effect and a favorable toxicity profile that allows these compounds to be considered promising leads and drug candidates for the treatment of HBV infection. The established alphavirus based HBc expression approach allows for the specific selection of capsid assembly modulators directly in the natural cell environment.